INDEX OF DIRECTION CHANGE OF ZONALLY AVERAGED WIND AND CHANGE OF SEASON - 朱敏 徐建霞 张铭 (Journal of Tropical Meteorology, 2011)
In this paper, a Wind Direction Change Index （WI）, which can describe four-dimensional spatiotemporal changes of the atmospheric circulation objectively and quantitatively, is defined to study its evolution and seasonal variation. The first four modes can be obtained by EOF expansion of the zonally averaged WI. The first mode reveals the basic spatial distribution of the annually averaged WI. The second mode reflects the quasi-harmonic parts of the WI deviations. Tropical, subtropical and extratropical monsoon areas can be clearly reflected by this mode. The third mode reflects the non-harmonic parts of the WI deviations. It shows the so-called February reverse in stratospheric atmosphere as well as the asymmetric seasonal changes from spring to fall and from fall to spring due to both the land-sea distribution contrast between the Northern and Southern Hemispheres and the nonlinear effect of atmospheric and ocean fluids. The fourth mode reveals the northward advancing of the global reversed wind fields from spring to summer and their southward withdrawal from summer to autumn.